Diseño y construcción de un dispositivo mediante un sistema embebido para pruebas de vulnerabilidad en redes 802.11 orientado a pequeñas y medianas empresas. - Quille Valverde, Jose Ángel (2023)
This study investigates the use of embedded systems to carry out penetration attacks against wireless networks. Two boards, the Raspberry Pi and the Banana Pi, are compared in a test environment to see which is the best option in terms of quality and cost. In addition, three Linux-based operating systems (Armbian, Raspbian, Kali) are examined to measure their impact on security testing. The effectiveness and ease of use of the tools used are also determined, as well as the impact of operating systems on their performance. To make the installation and use of the tools more accessible, a console executable software has been developed that allows installation of multi-dependency and vulnerability testing without the use of complicated commands. This solution streamlines the process of setting up the pentesting environment, which could save time and decrease the likelihood of user error. In addition, this tool has an intuitive and user-friendly interface, which is very useful for those who are not familiar with the command line. Users can work with the penetration testing tools without needing to learn the specific commands and syntax of each tool. Keywords: Raspberry, Banana, Linux, Kali, Armbian, Raspbian, Pentesting.